Relaksasi Kredit Pada Kepemilikan Rumah Subsidi Di Bank Mandiri Kota Medan Di Masa Pendemi Covid-19 Berdasarkan Peraturan Otoritas Jasa Keuangan - Medianson Saragih, Gema Medianson (Recital Review, 2021)
Covid-19 pandemic that occurs in Iitdonesia not only creates contagious disease resulting deaths, but also causes stagnancy in economic cycle of a country and its people. The policy of large-scale social restriction (PSBB) makes the company, factory, stores, supermarket and shopping centers temporarily stop their economic activities and terminate their employees. The results demonstrate that Bank Mandiri, as the lender, does not implement the policy of credit relaxation in the covid-19 pandemic to the debtors of subsidized mortgage in accordance with the law. Bank Mandiri makes special policy in the form of debtor classification, namely employees who have been terminated as the customers. External constraint comes from the debtors who state their inability to pay the installment of subsidized mortgage. Another constraint comes from the management of Bank Mandiri Medan City that has the technical implementation guidelines of credit relaxation distribution, based only on subjective assessment of the surveyor and the management of Bank Mandiri Medan City, guided by the justice limited by prudence principles. Â Â